GAMBARAN PENGGUNAAN OBAT OFF-LABEL PADA PASIEN ISPA DI RSUD PROVINSI NUSA TENGGARA BARAT TAHUN 2022 - Eryona Azizun Rosyida; Linda Oktavia Nensi; Anna Pradiningsih; Dzun Haryadi Ittiqo; G.A.P. Sri Erwinayanti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Acute Respiratory Infections (ARI) are a common disease in Indonesia, particularly among children, who are at risk of off-label drug prescribing due to limited pediatric efficacy and safety data. Off-label use includes off-label age, dose, indication, and route of administration. This observational, cross-sectional study aimed to describe the pattern of off-label drug use in ARI patients at the West Nusa Tenggara Provincial Hospital. Medical records of outpatients diagnosed with ARI between January and December 2022 were reviewed, with 80 patients meeting the inclusion criteria. The results showed that 27% of ARI prescriptions involved off-label use, exclusively in the off-label age category, with salbutamol being the most frequently prescribed off-label drug. This finding indicates a considerable rate of off-label drug use in ARI management, highlighting the need for collaboration between pharmacists and physicians to monitor such use. Further research is recommended to identify the risk factors and correlations associated with off-label prescribing for ARIs.